Protecting place through community alliances: Haida Gwaii responds to the proposed Enbridge Northern Gateway Project - Crist, Valine (2012)
This research contributes to the emerging dialogue concerning power relationships and the alliances that are challenging current frameworks in an attempt to create positive change. Worldwide, local people in rural places are threatened by development paradigms and conflicting social, political, economic, and ecological values. Large-scale development, such as the Enbridge Northern Gateway Project (NGP), provide a tangible example of our failing systems and make the interplay of these elements palpable. Increasingly, communities are coalescing to challenge the current models and economically motivated agendas threatening Indigenous sovereignty and local lifeways. Central to these coalitions are Indigenous peoples who are aligning with non-Indigenous neighbours to renegotiate power relationships. This research examines these dynamic alliances and uses Haida Gwaii’s resistance to the NGP as an example of the formidable strength of community coalitions mobilized by intersecting values. To contextualize the NGP within the broader discourse, I problematize Canada’s environmental assessment process and consider how media portrays the growing resistance to the proposed project. Drawing on information presented through the environmental assessment, I analyze the main messages and shared values of Haida Gwaii citizens opposed to the NGP. This thesis focuses on this unanimous and galvanizing resistance, which is largely motivated by the reliance on local food sources and an embodied connection to Haida Gwaii shared by Island citizens. The continued denial of Aboriginal title and rights was inherent throughout this consideration and is an underlying theme throughout the analyses. Graduate